2002
DOI: 10.1074/jbc.m208511200
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Gene Expression in Human Preadipocytes Is Switched on by Maturation-induced Demethylation of Distinct CpGs in Its Proximal Promoter

Abstract: The peptide hormone leptin plays a major role in the regulation of energy intake and expenditure and is predominantly expressed in mature adipocytes but not in preadipocytes. Using bisulfite genomic sequencing, we found that 32 CpGs, distributed within a 317-bp sequence of the proximal leptin promoter, were highly methylated in human preadipocytes (73.4% ؎ 9.0%). During maturation toward terminally differentiated adipocytes, this promoter region was extremely demethylated (9.4% ؎ 4.4%). CpG methylation-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
152
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(174 citation statements)
references
References 61 publications
12
152
1
3
Order By: Relevance
“…Consequently, we investigated whether insulin and hypoxia-mimetic agents might regulate the expression of the leptin gene in this cell context. The human leptin gene promoter is B3000 long and contains several regulatory motifs, including AP2, SP-1, CREB, C/EBP, GRE, CRE elements (Mason et al, 1998;Ahima and Flier, 2000;Melzner et al, 2002;Meissner et al, 2003). Most importantly, the promoter contains eight hypoxia-responsive elements (HRE) with the minimal core sequence 5 0 -RCGTG-3 0 that can recruit hypoxia-inducible factor (HIF) (Grosfeld et al, 2002;Meissner et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, we investigated whether insulin and hypoxia-mimetic agents might regulate the expression of the leptin gene in this cell context. The human leptin gene promoter is B3000 long and contains several regulatory motifs, including AP2, SP-1, CREB, C/EBP, GRE, CRE elements (Mason et al, 1998;Ahima and Flier, 2000;Melzner et al, 2002;Meissner et al, 2003). Most importantly, the promoter contains eight hypoxia-responsive elements (HRE) with the minimal core sequence 5 0 -RCGTG-3 0 that can recruit hypoxia-inducible factor (HIF) (Grosfeld et al, 2002;Meissner et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Lower methylation of LEP leads to increased expression and higher concentrations of leptin, which is illustrated by our finding of an increased leptin concentration with lower methylation of LEP. This is supported by the functional effect of methylation on leptin levels (7,12). The association between the duration of breastfeeding and LEP methylation is intriguing.…”
Section: Early Life Environment and Lep Methylationsupporting
confidence: 50%
“…The CpG sites studied in the LEP promoter show similar methylation in peripheral blood and adipocytes in vivo. Furthermore, methylation in adipocytes influences LEP expression in vitro (7,12). However, measurements of LEP mRNA have revealed that especially in children LEP is differentially expressed depending on the adipose region (34).…”
Section: Early Life Environment and Lep Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Twin studies show that DNA methylation and histone acetylation patterns diverged more strongly in older twin pairs with more marked life history differences [117] . It has been shown that the promoter in the leptin gene is subject to epigenetic programming and leptin gene expression can be modulated by DNA methylation [127][128][129] . Recent studies report that impaired glucose tolerance during pregnancy is associated with adaptations in leptin gene DNA methylation although the functional significance of these changes is not yet clear [130] .…”
Section: Role Of Epigeneticsmentioning
confidence: 99%